Arctic Marine Geophysics and Oceanography. - Hunkins,Kenneth (1970)
Contents: (Navigation, bathymetry, gravity, magnetics, seismic profiler, sound scattering layers, bottom photography and nephelometry); Ocean currents; and Hydroacoustics. See also AD-711 626.